A new species of the hermit crab genus Diogenes (Crustacea: Decapoda: Anomura: Diogenidae) from southern India - Komai, Tomoyuki; Reshmi, Rema; Kumar, Appukuttannair Biju (Zootaxa, 2013)
A new species of the hermit crab genus Diogenes Dana, 1851 (Diogenidae), D. canaliculatus, is described and illustrated on the basis of material from off the Kerala State, southern India. It is referred to the D. edwardsii (De Haan, 1849) species group, and compared with D. bicristimanus Alcock, 1905, D. fasciatus Rahayu & Forest, 1995, D. laevicarpus Rahayu, 1996 and D. moosai Rahayu & Forest, 1995. The characteristically sculptured left chela and the unarmed dorsal margins of the propodi of the second and third pereopods distinguish the new species from these congeners.